Re-thinking rights historical development and philosophical justification - Curran, Eleanor, 1956- (Lexington Books, 2022)
"This book takes a new look at the history of individual rights, focusing on how philosophers have written that history. Eleanor Curran argues that the turn to jurisprudence, after the philosophical rejection of natural rights, has resulted in an impoverished notion of rights as no more than claims and entitlements"--